Correlated, Dual‐Beam Optical Gating in Coupled Organic–Inorganic Nanostructures. Issue 36 (1st August 2018) - Wurst, Kai M.; Bender, Markus; Lauth, Jannika; Maiti, Sonam; Chassé, Thomas; Meixner, Alfred; Siebbeles, Laurens D. A.; Bunz, Uwe H. F.; Braun, Kai; Scheele, Marcus
Abstract: An optical switch with two distinct resonances is formed by combining PbS nanocrystals and the conductive polymer poly[sodium 2‐(2‐ethynyl‐4‐methoxyphenoxy)acetate] (PAE) into a hybrid thin film. Infrared excitation of the nanocrystals invokes charge transfer and consecutive polaron formation in the PAE, which activates the switch for excited‐state absorption at visible frequencies. The optical modulation of the photocurrent response of the switch exhibits highly wavelength‐selective ON/OFF ratios. Transient absorption spectroscopy shows that the polaron formation is correlated with the excited state of the nanocrystals, opening up new perspectives for photonic data processing. Such correlated activated absorption can be exploited to enhance the sensitivity for one optical signal by a second light source of different frequency as part of an optical amplifier or a device with AND logic. Abstract : IR‐active PbS nanocrystals were functionalized with poly(aryleneethynylene) π systems, resulting in a wavelength‐selective optical gate capable of the amplification of a first optical signal with a second light stimulus. This activated absorption is of interest for complex optical‐to‐electric data conversion.